CXCL12-induced chemotaxis is impaired in T cells from patients with ZAP-70-negative chronic lymphocytic leukemia - Borge, Mercedes (2010)
Background T cells from patients with chronic lymphocytic leukemia may play an important role in contributing to the onset, sustenance, and exacerbation of the disease by providing survival and proliferative signals to the leukemic clone within lymph nodes and bone marrow. Design and Methods By performing chemotaxis assays towards CXCL12, CCL21 and CCL19, we sought to evaluate the migratory potential of T cells from chronic lymphocytic leukemia patients. We next analyzed the chemokine-induced migration of T cells, dividing the chronic lymphocytic leukemia samples according to their expression of the poor prognostic factors CD38 and ZAP70 in leukemic cells determined by flow cytometry. Results We found that T cells from patients with chronic lymphocytic leukemia are less responsive to CXCL12, CCL21 and CCL19 than T cells from healthy adults despite similar CXCR4 and CCR7 expression. Following separation of the patients into two groups according to ZAP-70 expression, we found that T cells from ZAP-70-negative samples showed significantly less migration towards CXCL12 compared to T cells from ZAP-70-positive samples and that this was not due to defective CXCR4 down-regulation, F-actin polymerization or to a lesser expression of ZAP-70, CD3, CD45, CD38 or CXCR7 on these cells. Interestingly, we found that leukemic cells from ZAP-70-negative samples seem to be responsible for the defective CXCR4 migratory response observed in their T cells. Conclusions Impaired migration towards CXCL12 may reduce the access of T cells from ZAP-70-negative patients to lymphoid organs, creating a less favorable microenvironment for leukemic cell survival and proliferation.